A Compensation Measure of the cost of Unemployment to the Unemployed - Hurd, Michael (Quarterly Journal of Economics, 1980)
Under the assumption that unemployment is the result of job rationing, Hicks's compensating variation measures the payment that would make a worker indifferent between employment at his desired annual hours and rationed employment. This theory is applied at the individual level to find the compensation for the rationing. It varies according to the position of the compensated labor supply function, the wage rate, and the duration of unemployment. The individual measures are aggregated for each year from 1967 through 1975. The aggregate measure varies sharply with the level of unemployment; but it is small when compared with more conventional measures such as the difference between actual GNP and potential GNP.